2018
DOI: 10.3390/su11010082
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CO2 Emissions by Replacing an Ordinary Reinforced Concrete Slab with the Void Slab System in a High-Rise Commercial Residential Complex Building in South Korea

Abstract: The purpose of this study is to verify the environmental performance of the novel Void Deck Slab (VDS) system developed by the authors. The proposed VDS is a void slab system with enhanced design features that improve the constructability of the system through the elimination of additional works required to connect the void formers with the anchoring devices. The Life Cycle Assessment (LCA) technique was adopted to assess the carbon dioxide emissions of the void slab system with reference to the ordinary reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It should be noted that the building construction engineering includes three main parts: foundation engineering, structural engineering, and decoration engineering [29][30][31], which together constitute the carbon emission system of the whole building. This paper only studies the carbon emission system of PFS in structural engineering.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the building construction engineering includes three main parts: foundation engineering, structural engineering, and decoration engineering [29][30][31], which together constitute the carbon emission system of the whole building. This paper only studies the carbon emission system of PFS in structural engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Solid slab systems, an early innovation aimed at expediting construction and reducing costs by eliminating intermediate beams, remain one of the earliest methods introduced for such purposes [1,11,14]. Nevertheless, the substantial weight associated with this system renders it unsuitable for application in long spans and high-rise structures [10,[15][16][17][18]. Additionally, its increased weight contributes to heightened seismic loads, rendering its utilization in regions prone to high seismic activity economically unfeasible [4,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, its increased weight contributes to heightened seismic loads, rendering its utilization in regions prone to high seismic activity economically unfeasible [4,19,20]. Alongside the structural shortcomings, it is reported that the manufacturing processes of cement and rebars, which are the main components of concrete, entail substantial energy consumption and greenhouse gas emissions [15,16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that an increase in strength of the concrete resulted in an increase in the cost of CO 2 emission and concrete materials. Paik et al [13] evaluated the CO 2 emission of voided slab systems in comparison to conventional reinforced concrete slabs. They considered the raw materials and operation for the CO 2 calculations.…”
Section: Introductionmentioning
confidence: 99%